2015
DOI: 10.1016/j.jvs.2015.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications after common femoral endarterectomy

Abstract: CFE is not as "benign" a procedure as previously believed. The risks of death and wound complications are not insignificant, and a high percentage of these complications occurred after patients were discharged from the hospital. Patients should be carefully selected, especially in the elderly population, and close postoperative follow-up should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 9 publications
2
91
0
Order By: Relevance
“…[6] For comparison, a second study using a similar NSQIP sample to Nguyen et al, but excluding emergent cases, reported a 1.5% thirty-day mortality following isolated common femoral endarterectomy. [7] The later study did not identify proportion with rest pain and as mentioned above could not identify the proportion with CLI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] For comparison, a second study using a similar NSQIP sample to Nguyen et al, but excluding emergent cases, reported a 1.5% thirty-day mortality following isolated common femoral endarterectomy. [7] The later study did not identify proportion with rest pain and as mentioned above could not identify the proportion with CLI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the National Surgical Quality Improvement Program (NSQIP) evaluating isolated common femoral endarterectomy reported a 3.4% thirty-day mortality. [6] Siracuse et al, using NSQIP data from 2007–2010, found a thirty-day mortality rate of 1.5% for isolated common femoral endarterectomy but differed from the former in that it did not include emergent cases. [7] It is likely that many of the patients getting isolated common femoral endarterectomy, especially in the emergent setting, were too sick for a more extensive procedure, such as bypass.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our study, Nguyen et al recently reported in a large series that the risks of death following femoral endarterectomy, albeit as an isolated intervention, are not insignificant. 22 In addition, Hobo et al determined that surgical intervention for PAD, which included femoral endarterectomy, was associated with increased perioperative mortality. 6 The need for femoral endarterectomy is a reflection of extensive PAD, which is a well-established risk for adverse outcomes following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study of patients undergoing CFA endarterectomy demonstrated 30-day mortality and wound complication rates of 3.4% and 8%, respectively 44. Endovascular approaches to CFA revascularisation offer a minimally invasive alternative in patients who are not candidates for surgical endarterectomy.…”
Section: Treatmentmentioning
confidence: 99%